Corporate criminal liability under the Companies Act / Ramlah Hamid - Hamid, Ramlah (Faculty of Law, 1986)
Initially, it was said that a corporation had no mind, could not will, and so could not personally entertain the intent necessary to commit crimes. Powers were never explicitly conferred enabling the corporation to commit crimes. Therefore, it was said, the commission of any crime was necessary ultra vires a corporation and could not be imputed to it.But now, the question of whether a company ought, on grounds of public policy, to be made criminally liable has been answered in the affirmative by the courts. As we have seen now, the law which stands today is that a company may be prosecuted for the crimes of its officers or employees if the statute creating the offence is intepreted as imposing liability on the employer as well as on the officer or employee